Effects of bout duration on players` internal and external loads during small-sided games in young soccer players - Köklü, Y.; Alemdaroglu, U.; Cihan, H.; Wong, D. P. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To investigate the effects of different bout durations on internal and external loads of young soccer players during different small-sided games (SSGs). Methods: Fifteen young male soccer players (average age 17?±?1 y) participated in 2 vs 2, 3 vs 3, and 4 vs 4 SSGs. All games lasted 12 min playing time in total, but each SSG format further consisted of 4 bout durations: continuous (CON: 1 bout×12 min) or interval with short (SBD: 6 bouts ×2 min), medium (MBD: 3 bouts?×?4 min), or long (LBD: 2 bouts×6 min) bout durations. During the SSGs, heart-rate (HR) responses and distance covered in different speed zones (walking and low-intensity, moderate-intensity, and high-intensity running) were measured. Rating of perceived exertion (RPE) and blood lactate (La-) were determined at the end of each SSG. Results: The SBD format elicited significantly lower %HRmax responses compared to LBD and CON in all formats (P<.05). The SBD format also showed significantly shorter distances covered in walking and greater distances covered in moderate-intensity running, as well as significantly greater total distance covered compared to LBD and CON in all formats (P<.05). In addition, LBD produced significantly lower La- and RPE responses than SBD and CON in all formats (P<.05). Conclusions: These results suggest that coaches and sport scientists who want to achieve higher internal loads could use SBD and CON timing protocols, while those who want to achieve higher external loads might prefer to use SBD and MBD when planning all SSG formats.